Mechanistic Study of Lithium-Ion Battery Cathode Recycling Using Deep Eutectic Solvents - Alhashim, Salma H. (2023)
The colossal increase in the use of Lithium-ion batteries (LiBs) necessitates their efficient recycling to ensure a steady supply of essential cathode materials, e.g., Li, Co, and Ni, as well as to tackle huge bulks of battery waste. Deep Eutectic Solvents (DESs) are green solvents with immense potential in the hydrometallurgical recycling of LiB cathodes, although their leaching mechanism has not been explored. We investigate the leaching mechanism of the different transition metals (TM), e.g., Co, Ni, and Li, from the most abundantly used LiB cathode materials NMC and NCA in an ethylene glycol (EG):choline chloride(ChCl) based DES. Leaching experiments performed by altering different parameters and density functional theory (DFT) calculations imply that EG participates in H-bonding and weakens the metal-oxygen bond of the TMs, whereas Cl- attacks the metal center to form chlorometalate complexes. Li on the other hand is surrounded by Cl- ions and leached in the solution. The increased concentration of ChCl in DES ensures the facile formation of these complexes and enhances leaching.